Digital Marketing Socialization on the Development of Batik Nagari Tanjung Bonai Aur in Improving Marketing - Dedi Mardiansyah; Khairul Annisa Fitri; Muhammad Farid Islami; Muhammad Irfan Ghivari; Fanesha Andrica; Majid Muthahhari Manik; Rial Rifwandi; Vyola Maulana; Al Furqon; Ummi Hajra Dias; Ameera Iffa Zaafira (Universitas Lambung Mangkurat, 2024)
Tanjung Bonai Aur Batik, a mainstay product from Nagari Tanjung Bonai Aur in Sijunjung district, is a type of written batik that carries typical motifs from local culture. The rich culture of Minang inspires this batik motif. Even though we already have meetings at batik houses, further efforts are needed to increase Tanjung Bonai Aur Batik's understanding and popularity. One method of expanding the batik market is through digital marketing. By looking at these problems, this service activity was carried out to increase the marketing of Batik Tanjung Bonai Aur through socialization and digital marketing assistance. The results of this community service have implications for improving marketing and are expected to increase competitiveness and product sales more widely. The welfare of the people of Nagari Tanjung Bonai Aur can be further improved.